Prices and wages in U.S. manufacturing : a factor analysis - Barrett, Nancy Smith; Gerardi, Geraldine; Hart, Thomas P. (Lexington, Mass. : Lexington Books, 1973)
This book examines the inflationary process through every possible quantitative perspective.
Includes bibliographical references and index
mf24/01/2019
Loans
Keywords: Inflation (Finance); Prices; Wages